2018
DOI: 10.1021/acsami.7b19467
|View full text |Cite
|
Sign up to set email alerts
|

Nanochip-Induced Epithelial-to-Mesenchymal Transition: Impact of Physical Microenvironment on Cancer Metastasis

Abstract: Epithelial-to-mesenchymal transition (EMT) is a highly orchestrated process motivated by the nature of physical and chemical compositions of the tumor microenvironment (TME). The role of the physical framework of the TME in guiding cells toward EMT is poorly understood. To investigate this, breast cancer MDA-MB-231 and MCF-7 cells were cultured on nanochips comprising tantalum oxide nanodots ranging in diameter from 10 to 200 nm, fabricated through electrochemical approach and collectively referred to as artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, on the basis of these findings, we further explored the possible mechanisms underlying the effect of CD147 on the development and recurrence of OSCC, especially cervical lymph node metastasis. EMT was reported to be closely related to lymph node or distant metastasis in some malignant tumours, especially squamous cell carcinomas 6,28,29 . We found that E‐cadherin expression in the OSCC tissues was significantly lower than that in the adjacent oral mucosa.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, on the basis of these findings, we further explored the possible mechanisms underlying the effect of CD147 on the development and recurrence of OSCC, especially cervical lymph node metastasis. EMT was reported to be closely related to lymph node or distant metastasis in some malignant tumours, especially squamous cell carcinomas 6,28,29 . We found that E‐cadherin expression in the OSCC tissues was significantly lower than that in the adjacent oral mucosa.…”
Section: Discussionmentioning
confidence: 61%
“…Epithelial‐mesenchymal transition (EMT), a pathological process that polarizes epithelial cells to undergo various biological changes and obtain the phenotypes of mesenchymal cells, is considered to play an important role in invasion and metastasis during the progression of various cancers 5‐7 . Reduction of E‐cadherin is closely related to cancer cell EMT and leads to the loss of intercellular adhesion, destruction of the basement membrane morphology and subsequent decrease in the stability of the epithelium or vascular endothelium, thereby inducing metastasis 8‐10 .…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin gene expression decreased and N-cadherin and vimentin expression was enhanced. This is the case when epithelial cells are cultured on a microfluidic device with a flow of healthy serum and heat-inactivated serum with C3a stimulate mesenchymal and epithelial phenotypes, respectively [40]. On the other hand, the viscosity of the normal breast epithelial cell was higher than that of cancer cells.…”
Section: Mcf-7 Cells On Crosslinked and Non-crosslinked P(cl-co-dlla)mentioning
confidence: 99%
“…Nanotopographical cues can be utilized to understand the biophysical regulation of the cellular behavior . A plethora of nanotopographies such as nano‐dots, rods, wires, grooves, and pores have been engineered in the past to understand the regulation of cellular growth, function, adhesion, or differentiation. Studies have shown that precise control over cytoskeletal organization and cellular mobility can be achieved via 2D or 3D nanosurfaces .…”
Section: Introductionmentioning
confidence: 99%